Malawi Financial Sector Assessment Program : Contractual Savings - Insurance and Pensions - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
The penetration level of the insurance and pension sectors in Malawi is low, but it seems adequate as compared with other countries in similar stages of development. Concentration and costs are high, the regulatory framework is outdated or inexistent and supervision is weak. An innovative pilot experience of weather micro-insurance is a good example of private-public partnership to reduce vulnerability and extend benefits, but the coverage is still low. The project faces several challenges, one of them being the need to invest in weather technology. Cost benefit analysis of public projects in this area should take into consideration the possible positive social benefits of income security for vulnerable rural population. The analysis needs to take into account that possibilities to increase micro-insurance penetration may be affected by the level of education of farmers, as well as their specific knowledge of insurance products and their confidence in insurance companies. Life insurance and private pension plans have an acceptable level of development as substitute of the non-existing mandatory pensions for private sector workers, but they need a stronger supervision and regulation to enhance their benefits. Rules should seek to promote portfolio diversification, higher portability of pensions and old age income security through well defined benefit rules.